Optimization of solvency margin in family Takaful and Life Insurance Institutions in Malaysia: Application of Data Envelopment Analysis - Musliza Musa; Syed Musa Alhabshi; Razali Haron (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - The purpose of this paper is to present the findings of the study on optimizing solvency margin in family Takaful and life insurance institutions in Malaysia.Method - The population of this study is family Takaful and life Insurance Institutions in Malaysia during the period 2010 - 2019. The selection of samples in this study uses the purposive sampling method and selected 11 family Takaful and 14 life Insurance Institutions. The data were analyzed using Data Envelopment Analysis. Result - The results showed that for from 2010 to 2019, the family Takaful operators’ efficiencies are improving, whilst the life insurers have become less efficient even though their efficiency score is higher than the family Takaful operators. In terms of the optimum size (i.e., scale), the results are reversed which means that the family Takaful operators are still not at the optimum size but once they reach there, they could improve their efficiency substantially. However, for both family Takaful operators and life insurers, 2019 seems to dip their efficiency in terms of pure technical and also scale.Implication - The results of this research open a new way of measuring the efficiency of family takaful and life insurance not only in Malaysia but can be generalized to measure the efficiency level of family takaful and life insurance in general.Originality - This research is the first study that used the combination of inputs and outputs specifically for the family Takaful and life insurance institutions in Malaysia.